Optimizing Bhabinkamtibmas in Overcoming Drug Abuse in Adolescents in the Sidoarjo Police Legal Territory - Bima Adhibrata (Advances in Police Science Research Journal, 2021)
Globalization is a multidimensional process of social change that crosses national boundaries and makes the world's people more connected and more dependent on each other. Globalization occurs because humans are increasingly innovative and increasingly progressive and supported by advances in technology, especially communication and transportation technology, these two technologies make the distance is getting closer. One of the negative impacts of globalization is narcotics which includes transnational-crime. Based on the background of the existing problems, the author raised the title of the thesis Optimization of bhabinkamtibmas in tackling drug abuse in adolescents in the jurisdiction of the Sidoarjo Police. The purpose of this study was to describe the occurrence of drug cases that occurred in adolescents in the Sidoarjo area. The research was conducted at the Satbinmas Polrestabes Sidoajro using a qualitative approach. Primary data sources were obtained through interviews with sources in the research object. Data were analyzed during and after data collection through the stages of collecting, reducing data, presenting data and drawing conclusions. From the results of the discussion based on the existing conceptual literature and interviews, it was found that the performance of bhabinkamtibmas is influenced by many factors, from within the bhabinkamtibmas itself and from the community. The community also has an important role in helping bhabinkamtibmas carry out its duties, especially in the prevention of drugs, if the community is open to one another, there will definitely be no people who become victims of drug abuse, especially teenagers. The conclusion in this study shows that the role of Bhabinkamtibmas and the community is very influential in suppressing the number of drug crimes among teenagers